Teste de condutividade elétrica em sementes de Bowdichia virgilioides Kunth - Dalanhol, Samanta Jaqueline [UNESP] (2014)
The aim of this study was to adapt the methodology of electrical conductivity (EC) test and determine the physiological quality of seeds of B. virgilioides. Seeds were separated into three batches according to tegument color (1-yellow, 2-orange, and 3-red/black). The EC test analyzed three quantities of seeds (25, 50 and 100), three volumes of water (25, 50 and 100 mL), and six times of seed imbibition (12, 24, 36, 48, 60 and 72), at 25 °C with 6 replications. Germination test was employed to compare the results. The EC test allowed the differentiation of batches in three levels of vigor - the same was observed in germination test: batch 1 presented the best seed vigor, followed by batches 2 and 3. The use of 25, 50 or 100 seeds imbibed in 50 mL of water for 24 hours is recommended.